Idhthirâbât al-Nuthq al-‘Arabiy ladâ Talâmîdz al-Madâris al-Ibtidâiyyah bi Madînah Mâlâng wa Hulûluhâ - Dien Nur Chotimah; Sutaman Sutaman (Jurnal Internasional Pendidikan Bahasa Arab, 2022)
This study aims to describe, analyze the cause, and offer some alternative solutions to the problem of Arabic pronunciation disorders in the students of the madrasah ibtidaiyah in Malang city. With the consideration that the earlier the problem of pronunciation disorders in madrassa students is known, the sooner the cause and solution can be known. The research method used is a qualitative descriptive analysis method, with data collection techniques using observation, interviews and documentation. The results obtained in this study are a) there are four types of Arabic pronunciation disorders in madrasah ibtidaiyah’s students in Malang city, namely: omission, substitution, distortion and addition. The most numerous forms are omissions, and the least are additions; b) there are three factors that cause pronunciation disorders in students of madrasah ibtidaiyah in Malang city: psychiatric factors, physical factors and social factors; c) the solutions that can be used to overcome pronunciation disorders in students also involve three factors: psychiatric factors, physical factors, social factors, and learning factors.